Biophilic Design as a Tool to Enhance Environmental Performance Under Flyovers - Neveen Y. Azmy (JES: Journal of Engineering Sciences, 2024)
Due to the increase in population and movement between cities, the number of flyovers has increased to facilitate the move between different areas in cities that led to high car traffic. As a result, carbon emissions and pollution have increased, affecting the air temperature and quality in urban areas. Therefore, this paper studies how to improve the environmental performance under the flyovers in cities. The research’s aim can be fulfilled through biophilic design that works on the vitality of urbanization and integration with nature, as it promotes green infrastructure. This paper deals with the study of flyovers, their characteristics, and the necessary criteria for obtaining effective areas below them, biophilic design for urbanization, and the principles and criteria for its use to improve environmental performance under the areas of flyovers, with an analysis of examples of effective handling of flyovers. The paper focuses on a case study at the areas under the flyovers in Alexandria Square in Tanta city and its analysis before and after the biophilic treatment using the environmental simulation program Envi-met. The proposed design can reduce the value of PMV by about 35% from its current state during the hours of solar presence to achieve thermal satisfaction.